MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DALAM PEMECAHAN MASALAH MELALUI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) PADA MATERI SISTEM PERSAMAAN LINEAR - Eka Rahmawati Gunar; Bambang Agus Sulistyono; Darsono Darsono (UNEJ e-Proceeding, 2022)
The research was motivated by the results of the researchers' observations, namely the lack of student creativity in finding solutions to a problem due to the use of learning models that emphasize more on aspects of knowledge so that students' creative thinking skills are still lacking. Based on this background, the researchers applied the Creative Problem Solving (CPS) learning model where students were given the freedom to find new things in problem solving so that they could improve students' mathematical creative thinking skills. The research uses 3 indicators of creative thinking ability, namely fluency, flexibility, novelty. The research method used is a quantitative method with an experimental design of One-Group Pretest Posttest Design. The research sample was taken using Probability Sampling, the research data were obtained from the students' pretest posttest. Data analysis used descriptive statistics in the form of tables and diagrams. From the research results, each indicator has increased, namely the fluency indicator 45 percent, flexibility 40 percent, novelty 18 percent. Based on the increase in each indicator of creative thinking ability, it can be concluded that the use of the Creative Problem Solving (CPS) learning model in SPLTV learning can improve students' mathematical creative thinking skills in problem solving. Keywords: mathematical creative thinking skills, CPS learning model, problem solving, system of linear equations